2022
DOI: 10.1108/el-01-2022-0012
|View full text |Cite
|
Sign up to set email alerts
|

Linguistic archives and language communities questionnaire: establishing (re-)use criteria

Abstract: Purpose The purpose of this paper is to prepare data that can be used as a base for establishing best practices for making archival linguistic materials available for (re-)use by members of language communities. Design/methodology/approach To assess how archival materials can be made more readily available to marginalized language communities, the authors use a questionnaire targeted at their members and, to a lesser extent, outsider researchers worldwide. Findings The collected data shows certain peculiar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
0
0
Order By: Relevance
“…Yet, these goals and standards, e.g., for FAIR data [32], are concerned with the use and reuse by academics and not primarily with facilitating access and use by community members. They stand at the opposite end of the spectrum and will be, bar citizen science, more interested in the stories told by their relatives or neighbours, mediated by their personal experiences and interactions with the people [16]. The language documenters' conduct and personal interactions with the community are more relevant than the technical details of the language data -and these data sets, independent of their quality or relevance for linguistic enquiry, may be a symbol of historical injuries for the communities, as often encountered with older data sets [4,11].…”
Section: Humans In Linguistic Datamentioning
confidence: 99%
“…Yet, these goals and standards, e.g., for FAIR data [32], are concerned with the use and reuse by academics and not primarily with facilitating access and use by community members. They stand at the opposite end of the spectrum and will be, bar citizen science, more interested in the stories told by their relatives or neighbours, mediated by their personal experiences and interactions with the people [16]. The language documenters' conduct and personal interactions with the community are more relevant than the technical details of the language data -and these data sets, independent of their quality or relevance for linguistic enquiry, may be a symbol of historical injuries for the communities, as often encountered with older data sets [4,11].…”
Section: Humans In Linguistic Datamentioning
confidence: 99%
“…(Burke et al, 2022a, p. 10 [emphasis added]) As this language archive manager's experience demonstrates, user studies conducted on digital platforms may fall short in reaching language community audiences. Khait et al (2022) report preliminary results of an online survey about language community experiences with accessing digital material. The survey was completed by nine respondents from language communities in Africa, South America, Europe, and Asia, who indicated that they access language materials primarily on mobile devices and via social media platforms rather than the archival interface itself.…”
Section: Accessibilitymentioning
confidence: 99%
“…As the landscape of language archiving expands, we now see increased emphasis on the re-use of archival material (Olko & Wicherkeiwicz, 2016;Spence, 2018;Seyfeddinipur et al, 2019;Khait et al, 2022), particularly to support language revitalization-efforts to increase and maintain the use of the language. 2 There are calls for language documentation (and, by extension, language archiving) to become "revitalization-driven practice[s]" (Nathan & Fang, 2013, p. 42).…”
mentioning
confidence: 99%